Engineering and Innovations in Neurosurgery - Dabadi, Sambardhan; Raj Dhungel, Raju; Acharya, Saugat; Acharya, Samir; Shrestha, Janam; Dhakal, Sudan (Annapurna Journal of Health Sciences, 2023)
Introduction: Modern technology engineered and developed with artificial intelligence have significantly improved the nature of diagnosis and treatment of patients. Healthcare facility has changed significantly in the past few decades because of technological developments. Neurosurgery has been able to practise and enjoy a lot of technologically advanced tools in the past few decades. In context of Nepal, technologically sophisticated devices and tools ranging from neuro navigation, high speed cutting drills, intra operative neuro monitoring, deep brain stimulation, to high resolution magnetic resonance imaging are already introduced. In this paper, the literature review on currently available technologies used in neurosurgery, their significance in delivering a better health care and their usage in Nepal has been discussed.